2020
DOI: 10.1007/s12192-020-01095-z
|View full text |Cite
|
Sign up to set email alerts
|

Small heat-shock proteins and their role in mechanical stress

Abstract: The ability of cells to respond to stress is central to health. Stress can damage folded proteins, which are vulnerable to even minor changes in cellular conditions. To maintain proteostasis, cells have developed an intricate network in which molecular chaperones are key players. The small heat-shock proteins (sHSPs) are a widespread family of molecular chaperones, and some sHSPs are prominent in muscle, where cells and proteins must withstand high levels of applied force. sHSPs have long been thought to act a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 115 publications
3
41
0
Order By: Relevance
“…Accordingly, interference with HSPB7 expression in zebrafish and human cardiomyocytes also results in increased load by damaged proteins and stimulation of autophagic pathways [ 50 ]. Further studies are necessary to resolve the cause for its strongly reduced expression in our Hom mice, and to elucidate its precise role, both in actin-based assembly and regulation of autophagic pathways [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, interference with HSPB7 expression in zebrafish and human cardiomyocytes also results in increased load by damaged proteins and stimulation of autophagic pathways [ 50 ]. Further studies are necessary to resolve the cause for its strongly reduced expression in our Hom mice, and to elucidate its precise role, both in actin-based assembly and regulation of autophagic pathways [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Included in the Hsp family are small heat shock proteins (sHsps), which are ubiquitously expressed regulators of cellular protein folding [ 30 ]. The high expression of sHsps in the heart has been reported, where they are implicated in the maintenance of normal cardiac function and regulation of the cardiac stress response [ 50 , 51 ].…”
Section: An Emerging Field: Heat Shock Protein and Molecular Chapementioning
confidence: 99%
“…13 Studies have shown that chaperones like α β crystallin or calreticulin has played crucial role in deciding mechanical properties of cell, like resilience of cell adhesion, cell spreading, by regulating expression of key focal adhesion proteins. 13,14 Small heat shock proteins have also been observed to regulate chronic biomechanical stress in heart tissue by regulating dynamics of key FA protein like actin and filamin C. 17 Additionally, tension-induced ubiquitylation of filamin A promotes chaperone-assisted autophagy which in turn dictate the role of chaperones in focal adhesion assembly. 35,36 However, the underlying molecular mechanism of these chaperone interactions, during mechanotransduction, has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%